Recycling Materials Based on Environmentally Friendly Techniques - Achilias, Dimitris S. (IntechOpen, 2015)
Reducing the amount of solid wastes in landfills is one of the main targets in nowadays wastes treatment. To this direction, there is a great need in finding of smart recycling techniques which should, as is possible, to be environmentally friendly. The intention of this book is to present some recent methods for the recycling of several materials, including plastics and wood, as well as to show the importance of composting of polymers. It targets professionals, recycling companies, researchers, academics and graduate students in the fields of waste management and polymer recycling in addition to chemical engineering, mechanical engineering, chemistry and physics. This book comprises 5 chapters covering areas such as, recycling of polystyrene, polyesters, PC, WEEE and wood waste, together with compostable polymers and nanocomposites.